Rare and Exotic Orchids Their Nature and Cultural Significance - Schiff, Joel L. (Springer International Publishing, 2018)
Comprising some 28,000 different species, orchids are by far the largest flowering plant family on Earth. Every year, new species are being uncovered in the wild or created by humans, and so this number has only continued to blossom. This book is intended for those who wish to learn about the multifaceted nature of this amazing plant. It covers many different aspects of orchid study, from its cultural history to its evolutionary development and from its first discoveries to ongoing scientific research. No matter your specialty or level of orchid expertise, you can find in this book new and fascinating facts and stories that will make you gasp, laugh, and read on. Through the many exotic and beautiful pictures permeating these pages, you will come to know something of the infinite diversity of this plant family and at last learn why so many orchid growers and fanatics have embarked on this same endless, flowering path.